(untitled) (Experimental biology, 2020)
Transcription factors (TFs) are the most important proteins in expression of genes and genomes in general. MYB TFs family in animals is little studied and it is necessary to ascertain their properties. In recent years, effect of miRNA on gene expression has been actively studied, since the degree of miRNA influence on expression turns out to be key and determines differentiation, proliferation, cell cycle, apoptosis and other important biological processes. MirTarget program makes it possible to predict miRNA binding characteristics of mRNA with high efficiency, to obtain highly reliable interaction properties of miRNA with MYB family TFs mRNA. Binding characteristics of known miRNAs and mRNA genes of Bos taurus, Equus caballus, Ovis aries MYB family TFs were established. Only 13 bta-miRNAs had binding sites with more than 87%ΔG/ΔGm value in B.taurus TF genes mRNA. mRNA of DNAJC2, MYB, MIER2, MYBL1, MYBL2 genes had only one binding site for different miRNAs. NCOR1 mRNA had binding sites for three miRNAs, located a few hundred nucleotides in CDS. RCOR1 was targeted by five miRNAs that had 14 binding sites. miR-2885, miR-11976, and miR-11975 binding sites were located with nucleotide sequences overlapping in mRNA cluster from 147 nt to 168 nt. These miRNAs had five binding sites in second cluster from 177 to 216 nt. Third cluster of miR-2305, miR-11976, miR-11975 binding sites is localized from 222 to 256 nt. For E.caballus established binding sites of 15 miRNAs with mRNA of ten genes of MYB family. mRNAs of MIER1, MYBL2, RCOR2, RCOR3, SMARCA5, SMARCC2, TERF2 genes can bind with one miRNA. For O.aries, we established ten miRNA binding sites with mRNA of eight genes of MYB family. mRNA of CDC5L, MIER1, MYSM1, RCOR1, RCOR2, RCOR3, SMARCA1 genes can bind with one miRNA with ∆G/∆Gm ratio from 86% to 89%. Кey words: miRNA, gene, MYB, B. taurus, E. caballus, O. aries.